IMPLEMENTASI PROGRAM LITERASI PERPUSNAS DALAM RANGKA PENINGKATAN MINAT BACA ANAK ANAK SD MELALUI KEGIATAN KKN DI DESA MARONG, KECAMATAN PRAYA TIMUR - Alfarid, Muhamad; Jurnal Wicara; Zulfa, Atika; Ray, Vrannya; Nasuha, Lale; Maharani, Nabilla; Aldy, Lalu; Raditya, I; Husmawati; Lestari, Wahyuni; Farizi, Muhammad; Alfarid, Muhammad (Universitas Mataram, 2025)
This study examines the implementation of a literacy program initiated by the National Library of Indonesia (Perpusnas) through the Community Empowerment Village Service-Learning Program (KKN PMD) in Marong Village, East Praya District, Central Lombok Regency. The main focus of this research is to increase the reading interest of elementary school students who have long faced limited reading facilities, minimal learning assistance, and low community awareness of the importance of sustainable basic literacy. This research employed a descriptive qualitative method with purposive sampling techniques, in which data were collected through interviews, observations, and documentation involving teachers, the managers of the Community Reading Park (TBM) Semeton Bace, village officials, parents, and students. The findings show that literacy activities, including school literacy visits, book-based project development, optimization of the role of TBM, improvement and decoration of reading facilities, as well as literacy competitions, have succeeded in increasing reading enthusiasm as well as collective community awareness. Supporting factors include the availability of engaging illustrated books, intensive mentoring by university students, and active promotion of TBM as an alternative learning space. Nevertheless, the sustainability of the program requires a long-term commitment from schools, TBM, and village governments to ensure that literacy culture can be maintained. The study highlights that multi-stakeholder collaboration and the implementation of creative literacy strategies are effective solutions to address low reading interest among rural children while also building a foundation for sustainable community education.